Seasons in parenting studies on parents' life stories and parenting achievements - Javier, Roberto E. Jr. (Manila published and distributed by De La Salle University Publishing House, 2015)
"Seasons in Parenting presents studies on the achievements of parents and their life stories."--Back Cover
Includes bibliographical references (pages 170-177).
In English.
Keywords: Parenting -- Philippines; Child rearing -- Philippines; Child development -- Philippines